2005
DOI: 10.1080/00222340500251394
|View full text |Cite
|
Sign up to set email alerts
|

Structure/Property Relationships for Poly(Vinylidene Fluoride)/Doped Polyaniline Blends

Abstract: Poly(vinylidene fluoride) (PVDF) and its blends with polyaniline (PANI) doped with dodecylbenzene sulfonic acid (DBSA) were characterized by electrical conductivity, differential scanning calorimetry (DSC) and X-ray scattering techniques.The onset of an infinite cluster (InC) of conducting, highly anisometric PANI/ DBSA particles in PVDF/(PANI/DBSA) blends was observed at the percolation threshold as low as w à % 3.5 wt.%. The small angle X-ray scattering (SAXS) data confirmed the expected spatial organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…4). The similarity of observed intensity decays at q < 0.14 A À1 suggests the absence of both large-scale and lower-scale structural heterogeneities in PANI nanocomposites, 44 whereas the well-resolved SAXS reections near q ¼ 0.204 A À1 (PANI/DBSA) and 0.180 A À1 (PANI/LSA) corresponding to mean interchain distances of d ¼ 2p/q z 3.1 nm and 3.5 nm respectively can be seen. Summarizing the above, we suggest a specic non-structured polymer condition in the composites due to small thickness of the layers (shells) covering TiO 2 nanoparticles.…”
Section: The Nanocomposites Structurementioning
confidence: 74%
“…4). The similarity of observed intensity decays at q < 0.14 A À1 suggests the absence of both large-scale and lower-scale structural heterogeneities in PANI nanocomposites, 44 whereas the well-resolved SAXS reections near q ¼ 0.204 A À1 (PANI/DBSA) and 0.180 A À1 (PANI/LSA) corresponding to mean interchain distances of d ¼ 2p/q z 3.1 nm and 3.5 nm respectively can be seen. Summarizing the above, we suggest a specic non-structured polymer condition in the composites due to small thickness of the layers (shells) covering TiO 2 nanoparticles.…”
Section: The Nanocomposites Structurementioning
confidence: 74%
“…Structure differences between the conducting polymer in pure and composite states were confirmed for different (nano)composites [16,17,19,23,25,26,29,[30][31][32][33]. For example, from the XRD-spectra of doped polyaniline and its nanostructured composite with polycarbonate (PC), we found that its degree of crystallinity in the pure state was about 3 times lower, and 6.…”
Section: Structure-property Relationship Of the Nanocompositesmentioning
confidence: 81%